Reducing Capacity and Voltage Decay of Co‐Free Li1.2Ni0.2Mn0.6O2 as Positive Electrode Material for Lithium Batteries Employing an Ionic Liquid‐Based Electrolyte. Issue 34 (23rd July 2020) - Wu, Fanglin; Kim, Guk‐Tae; Diemant, Thomas; Kuenzel, Matthias; Schür, Annika Regitta; Gao, Xinpei; Qin, Bingsheng; Alwast, Dorothea; Jusys, Zenonas; Behm, Rolf Jürgen; Geiger, Dorin; Kaiser, Ute; et al.
Abstract: Lithium‐rich layered oxides (LRLOs) exhibit specific capacities above 250 mAh g −1, i.e., higher than any of the commercially employed lithium‐ion‐positive electrode materials. Such high capacities result in high specific energies, meeting the tough requirements for electric vehicle applications. However, LRLOs generally suffer from severe capacity and voltage fading, originating from undesired structural transformations during cycling. Herein, the eco‐friendly, cobalt‐free Li1.2 Ni0.2 Mn0.6 O2 (LRNM), offering a specific energy above 800 Wh kg −1 at 0.1 C, is investigated in combination with a lithium metal anode and a room temperature ionic liquid‐based electrolyte, i.e., lithium bis(trifluoromethanesulfonyl)imide and N ‐butyl‐ N ‐methylpyrrolidinium bis(fluorosulfonyl)imide. As evidenced by electrochemical performance and high‐resolution transmission electron microscopy, X‐ray photoelectron spectroscopy, and online differential electrochemical mass spectrometry characterization, this electrolyte is capable of suppressing the structural transformation of the positive electrode material, resulting in enhanced cycling stability compared to conventional carbonate‐based electrolytes. Practically, the capacity and voltage fading are significantly limited to only 19% and 3% (i.e., lower than 0.2 mV per cycle), respectively, after 500 cycles. Finally, the beneficial effect of the ionic liquid‐based electrolyte is validated in lithium‐ion cells employing LRNM and Li4 Ti5 O12 . These cells achieve a promising capacity retention of 80% after 500 cycles at 1 C. Abstract : This work demonstrates the excellent performance of cobalt‐free Li1.2 Ni0.2 Mn0.6 O2 (LRNM) as a next‐generation high‐energy cathode material in combination with an ionic liquid‐based electrolyte (0.8Pyr14 FSI‐0.2LiTFSI) under room temperature conditions. The use of this electrolyte dramatically reduces the capacity and voltage fading of the LRNM cathode in lithium metal and lithium‐ion batteries.